Factors influencing operations management practices for Islamic banks in Bangladesh - Nahar, Rezbin; Islam, Rafikul (Islami Bank Training and Research Academy, 2016)
Successful Operations Management Practices (OMP) has a lasting impact on a company’s overall performance. This paper explores the factors influencing OMP in the context of Islamic banks in Bangladesh. A focus group method was used to collect data to clarify the themes of OMP. A survey questionnaire was then distributed to determine the influential OMP factors through an Exploratory Factor Analysis. Operations Strategy, Quality and Satisfaction as well as Productivity and Relationship with Suppliers were found to be the most influential factors of OMP for Islamic banks in Bangladesh. Subsequently, a model has been created through multiple regression analysis that portrays the relationship among dependent and independent variables. The results show that Quality and Satisfaction, Productivity and Relationship with Suppliers are significantly related with OMP for Bangladeshi Islamic banks. The research findings are expected to provide guidelines for designing effective OMP specifically for Islamic banks in Bangladesh, but have a wider relevance to the Islamic banking industry as a whole. The findings of this study will also assist managers of banks and financial institutions to invest their resources more efficiently.